(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article analyzes the current state and problems of product production in the province of Namangan on the basis of international standards (ISO) in business entities on the basis of official statistics and scientific literature. In the 2024-2025 section, the network and technological composition of the industry of the region, the number of enterprises and the dynamics of production volumes are summarized. The results showed that the textile/clothing and food industries are dominant in Namangan, the high-tech segment share is low, and the introduction of standards in these conditions can be the main driver for the internal process efficiency of enterprises and their adaptation to exports. The problems were broken down into financial, technological, human resources and institutional barriers, and factors such as the lack of documentation and knowledge found in the introduction of HACCP/ISO 22000 in food were compared to scientific literature. At the end of the study, a “barrier matrix” in the cross section of fields for Namangan and practice-oriented recommendations for business entities were given.